2020
DOI: 10.1111/imig.12709
|View full text |Cite
|
Sign up to set email alerts
|

We Don’t Belong Here: Adolescents of North Korean Refugee Families and Their Suicidal Behaviors

Abstract: Despite the increasing number of studies that examine the link between immigration and suicide in Korean youths, most have focused on self-harming behaviours among adolescents in multicultural families, while much less attention has been directed towards those in North Korean (NK) refugee families. This paper addresses this gap by comparing three determinants of suicidal behaviours across three groups of Korean adolescents. Data are drawn from the KYRBS, a nationally representative sample of students in middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 26 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Among the studies using general samples, 15 [ 17 , 18 , 20 , 30 , 39 , 47 49 , 54 , 55 , 77 , 79 , 83 , 85 , 88 ] reported on the prevalence of suicide attempts ( Table 3 ). The results are ordered by timeframe for the prevalence estimates and then sub-grouped by population type.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the studies using general samples, 15 [ 17 , 18 , 20 , 30 , 39 , 47 49 , 54 , 55 , 77 , 79 , 83 , 85 , 88 ] reported on the prevalence of suicide attempts ( Table 3 ). The results are ordered by timeframe for the prevalence estimates and then sub-grouped by population type.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies in general samples compared the prevalence of suicide attempts in displaced people to the host population. Only five of these studies [ 20 , 30 , 54 , 77 , 81 ] reported data in formats that could be presented visually in forest plots ( Fig 3 ). Two of these studies were in refugees granted asylum, one was in mixed refugees & asylum seekers, one was in internally displaced people, and one was a pooled report of mixed refugee populations across 21 countries [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations